2022
DOI: 10.3390/clinpract12030045
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Utility of ABO and RHD Systems as Potential Indicators of Health Status, a Preliminary Study in Greek Population

Abstract: Objective: The objective of this study is to further highlight the differences between different ABO blood groups and Rhesus types with health biomarkers. Methods: In total 150 active healthy blood donors participated in our study comprising of 80 males from 19–61 years and 70 females aged from 21 to 64. Participants carrying blood group A were 55 individuals, blood group B 32, blood group O 51, and blood group AB 12, RHD+ 132, and RHD- 18. All the volunteer regular blood donors were selected recognizing them … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 54 publications
0
2
1
Order By: Relevance
“…The mechanism for the association of RhD− individuals with subclinical atherosclerosis might be related to the fact that lipoproteins have been shown to differ between RhD groups but not between ABO groups [ 13 ]. However, one study reported a better lipid profile in RhD− compared to RhD+ individuals [ 14 ], which contradicts our results. Another mechanism that may contribute to the increased risk for subclinical atherosclerosis observed in RhD− individuals is hypertension.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…The mechanism for the association of RhD− individuals with subclinical atherosclerosis might be related to the fact that lipoproteins have been shown to differ between RhD groups but not between ABO groups [ 13 ]. However, one study reported a better lipid profile in RhD− compared to RhD+ individuals [ 14 ], which contradicts our results. Another mechanism that may contribute to the increased risk for subclinical atherosclerosis observed in RhD− individuals is hypertension.…”
Section: Discussioncontrasting
confidence: 99%
“…The ABO blood group system has previously been associated with several circulatory diseases [ 5 , 6 , 7 ], and it is stated that non-O blood group individuals are associated with increased incidence of arterial thromboembolic events [ 8 , 9 , 10 ], such as myocardial infarction (MI), but there are more conflicting results as to whether other forms of CVD are associated [ 10 , 11 , 12 ]. Few studies are available on the RhD blood group and its role in the pathogenesis of circulatory disease, but some have suggested that there are associations between RhD and dyslipidemia, which is a risk factor for CVD [ 13 , 14 ]. Studies assessing the roles of ABO and RhD in subclinical atherosclerosis as potential risk markers are sparse, and the studies available have primarily included individuals already considered high-risk.…”
Section: Introductionmentioning
confidence: 99%
“…The study was done in Blood Transfusion Center Oradea, Bihor County. There were used: medical records, and donors' files, where we noticed (paper and electronical support)/explained and managed each situation, from clinical and laboratory paraclinical points of view [1][2][3]. Was analised the activity along the year 2021, represented by 11839 blood donations (total blood and platelets apheresis) collected from 6913 blood donors.…”
Section: Methodsmentioning
confidence: 99%